PENGEMBANGAN MODEL KEPEMIMPINAN KI HAJAR DEWANTARA MELALUI PROGRAM GERAKAN SEKOLAH SEHAT UNTUK PEMBENTUKAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB SISWA DI SMP - Oktin Widayanti; Dewi Apriani; Beni Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop and implement the Healthy School Movement (GSS) program based on the leadership values of Ki Hajar Dewantara to foster students’ discipline and sense of responsibility at SMP Negeri 8 Pemalang. The background of the research is the low level of student discipline, lack of responsibility regarding cleanliness and health, and the suboptimal implementation of systematic character building within the school environment. The research adopts a Research and Development (R&D) approach using a modified Borg & Gall model consisting of five stages: needs analysis, program design, development, limited-scale implementation, and evaluation. The needs analysis revealed weaknesses among students in maintaining personal hygiene, punctuality, and healthy lifestyle habits. The GSS program was designed to integrate character education values through regular activities such as morning exercises, healthy breakfast routines, communal clean-up efforts, and attitude reflection. The instruments and program guidebooks were tested for content, construct, and empirical validity, with results indicating “valid” to “highly valid,” demonstrating the program’s theoretical and practical feasibility. Implementation in class VIII  showed significant improvements in student discipline, engagement, and responsibility. Teacher evaluations and student self-assessments categorized the program as “good” to “very good,” though the attitude reflection component requires further reinforcement through regular guidance. Feedback from both teachers and students serves as the basis for program refinement and future broader, sustainable implementation. Overall, the GSS program is proven effective in developing students’ character when carried out in a structured, participatory, and consistent manner.